Tanggung Jawab Sosial Perusahaan dalam Perspektif Islam (ICSR) dan Implikasinya bagi Reputasi Bank Syariah - Intan Darmawan; Ahmad Mifdlol Muthohar (JURNAL EKOMAKS Jurnal Ilmu Ekonomi Manajemen dan Akuntansi, 2026)
This study aims to analyze the influence of Islamic Corporate Social Responsibility (ICSR) on corporate reputation, particularly in the Islamic banking industry in Indonesia. This study employed a descriptive qualitative approach, employing desk research and literature mapping analysis. This approach was chosen because the research objective was to understand and explain the relationship between Islamic Corporate Social Responsibility (ICSR) and corporate reputation. The analysis was conducted using a literature review and literature mapping approach, thus revealing the pattern of ICSR's influence on corporate reputation from various research perspectives. The results indicate that most studies found a positive and significant effect of ICSR on corporate reputation. However, several studies found insignificant results, emphasizing the importance of the quality of ICSR implementation and stakeholder perceptions in building corporate reputation. This research is expected to serve as a reference for corporate management and academics in understanding the role of mortgages in enhancing reputation, while also contributing to the development of business practices that comply with Sharia principles.